2012
DOI: 10.24135/pjr.v18i2.270
|View full text |Cite
|
Sign up to set email alerts
|

FRONTLINE: An innovative direction in academic journalism

Abstract: The Pacific Media Centre—Te Amokura—which publishes Pacific Journalism Review has always been concerned to link ‘robust and informed journalism’ with media research that contributes to social development both in the broader community, the media industries and inside the academy. The new section Frontline aims to further this by addressing more directly the interface between professional or practice-based journalism and scholarly journalism research practices. This commentary reflects new directions in academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…There may be elements in this work that apply to other, unique practice situations (Schön, 1971), but I do not claim that this one example of journalism practice, or of research into this practice, can be generalised. However, acknowledging those who have argued for this approach before me (such as Bacon 2006aBacon , 2006bBacon , 2012Bromley 2006;McIntyre 2006;Niblock 2007), I advocate critical reflexivity as a suitable approach for researching at least some instances of the social practice of investigative journalism.…”
mentioning
confidence: 89%
“…There may be elements in this work that apply to other, unique practice situations (Schön, 1971), but I do not claim that this one example of journalism practice, or of research into this practice, can be generalised. However, acknowledging those who have argued for this approach before me (such as Bacon 2006aBacon , 2006bBacon , 2012Bromley 2006;McIntyre 2006;Niblock 2007), I advocate critical reflexivity as a suitable approach for researching at least some instances of the social practice of investigative journalism.…”
mentioning
confidence: 89%
“…The use of journalism as a research methodology to document the changes in Onslow was inspired by the academics who have argued that there is potential for journalism to be more widely used as a research methodology in Australia (Lamble, 2004;Nash, 2013;Bacon, 2006). Nash (2013) suggested that academics formulate a definitive definition of journalism as research, so as to engage with the ontological and epistemological systems in operation.…”
Section: Tracking Onslowmentioning
confidence: 99%
“…Mason (2014) also promotes critical reflexivity as a valid method in which to examine journalism from the inside, and suggests this process can facilitate greater understanding of journalism practice and its place in the societal sphere. Her argument builds on Bacon's (2006) assertion that journalism has a lot to do with the day-to-day exercise of power, and that reflexivity about standard journalism practices, such as consideration of whose voices are being privileged (and why), can improve the quality of the work being created and bring new insights. Andrejevic (2008) expands on this in his discussion of Foucault's power/knowledge discourses and argues that through Foucault, journalism can engage in reflexive critique and negotiate relationships of power as instruments of resistance.…”
Section: Tracking Onslowmentioning
confidence: 99%
“…However, efforts to revive investigative journalism in schools and practised journalism are considerable (Bacon, 2012;Richards & Josephi, 2013). Postmodern culture discussed social and ethic significant aspects, including the media, the way that major events in community are communicated to public.…”
Section: Introductionmentioning
confidence: 99%